2023
DOI: 10.1063/5.0140098
|View full text |Cite
|
Sign up to set email alerts
|

Flow control effect of pulsed arc discharge plasma actuation on impinging shock wave/boundary layer interaction

Abstract: The current study investigates the control effect of the pulsed arc discharge plasma (PADP) on the impinging shock wave and boundary layer interaction (SWBLI) generated by a 14{degree sign} wedge in a Mach 2.5 flow. The response characteristics of SWBLI on pulsed arc discharge (PAD) actuation were illustrated, and the controlling mechanism of shock-induced flow separation under different plasma power settings was revealed. The results showed that when setting the exciting power density ph as 1.0×1011 W/m3, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11] In particular, MAVs have attracted much attention [3][4][5][6][7][8][9][10][11] because of the ability to slip through bushes and excellent mobility to escape from enemies, which were previously only possible in creatures such as insects and birds. For example, Bachmann et al 7) reported a small (30.5 cm wingspan), lightweight (∼100 g) carbon fiber vehicle using a small motor that can fly, while Ma et al 12) developed a biologically inspired insect-scale robot and demonstrated tethered but unconstrained stable hovering. Furthermore, Chen et al 4) reported the controlled flight of a microbot powered by soft artificial muscles, while Wang et al 5) reported a bio-inspired rotary flight of lightdriven composite films.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] In particular, MAVs have attracted much attention [3][4][5][6][7][8][9][10][11] because of the ability to slip through bushes and excellent mobility to escape from enemies, which were previously only possible in creatures such as insects and birds. For example, Bachmann et al 7) reported a small (30.5 cm wingspan), lightweight (∼100 g) carbon fiber vehicle using a small motor that can fly, while Ma et al 12) developed a biologically inspired insect-scale robot and demonstrated tethered but unconstrained stable hovering. Furthermore, Chen et al 4) reported the controlled flight of a microbot powered by soft artificial muscles, while Wang et al 5) reported a bio-inspired rotary flight of lightdriven composite films.…”
Section: Introductionmentioning
confidence: 99%